PENGARUH KOMPETENSI TERHADAP KINERJA PEKERJA PADA PEMBANGUNAN PROYEK SWALAYAN PT. OASIS RUMAH TIGA KOTA AMBON - WANCE, SRI NUNUNG (NAROTAMA JURNAL TEKNIK SIPIL, 2023)
Abstract Many workers, especially handymen, do not meet competency standards. To achieve maximum and satisfactory work results, it is necessary to have competence possessed by a worker in carrying out his work duties so that worker performance can increase. The purpose of this research is to find out how the influence of competence on project performance and whether there is a significant relationship between competence and performance in the development. The research method used with the help of the SPSS version 16 program for data processing is to test the instrument, test the validity and reliability. Hypothesis tests include the F test (Anova) and the T test are used for data analysis on the test. The results obtained the following conclusions: Knowledge with an output value of tcount 0.345 < 2.100 and the probability value of the variable is sig = 0.735 > 0.05, so that the indicator of knowledge partially has a strong and significant relationship to performance. Skills with an output value of tcount -2.431 < 2.100 and the probability value of the variable sig = 0.027 < 0.05, so that the skill indicator has a weak relationship with performance. Meanwhile, the relationship between behavior and performance of the t-output valuecount -1.381 2.100 and the probability value of the indicator variable is sig = 0.186 > 0.05 partially has a weak relationship. Therefore, the researcher recommends for each construction project development in order to further improve the competence and performance of workers on each project. Keywords: competence, worker performance, construction project.